La professionnalisation de la conservation-restauration et ses limites : une analyse à deux voix - Léonie Hénaut; Anne-Elizabeth Rouault (In Situ)
This article is a dialogue between a professional curator and a sociologist about heritage conservation and restoration in France. Three questions are currently worrying the profession: who are the curators, how do they collaborate with other professionals and how is the market regulated outside the museum? Qualitative and quantitative data, and a case study, are presented to explore the developments and the limits of the professionalisation of conservators.